MEMUTUS RANTAI PENULARAN COVID-19 DENGAN MENERAPKAN PROTOKOL KESEHATAN 5 M PADA ANAK SEKOLAH DI TAMAN BACAAN PERIGI YANG BERTEPAT DI JALAN PAHLAWAN NO.48 RT.04/RW.07 KEDAUNG, SAWANGAN, DEPOK - Krisna Priyoadi; Widia Astuti; Muhamad Lavif; Muhammad Sopian; Pinsa Noor Septa; Dwi Gusmantri (Jurnal Lokabmas Kreatif : Loyalitas Kreatifitas Abdi Masyarakat Kreatif, 2021)
Health education and promotion plays a major role in handling COVID-19. During the pandemic, the government has recommended all citizens to apply 5 M, namely using masks, washing hands, and maintaining distance. With good health education and promotion, the level of spread of COVID-19 can be reduced. Education is one of the public health efforts to prevent the spread of COVID-19. One of the prevention and control of COVID-19 is by giving vaccines. However, until now the COVID-19 vaccine is still in clinical trials and there is no COVID-19 vaccine that has been approved for administration to patients. Vaccinations in the future are expected to help achieve herd immunity. Health promotion regarding how to prevent COVID-19 is very important to be given to the community. In addition, information about the mode of transmission and the severity of the disease can also be provided to increase public awareness. Information can be provided through social media and printed media, such as posters and pamphlets.